The importance of preparation for doctors' handovers in an acute medical assessment unit: a hierarchical task analysis. - Taduma-Tomàs, Michelle A; Flin, Rhona; Yule, Steven; Close, Steven (BMJ Quality & Safety, 2012)
AIM: To examine the ideal and actual processes of doctors' handovers in an acute medical assessment unit by means of a hierarchical task analysis (HTA) to identify any discrepancies between the ideal shift handover process as described by doctors, and the actual shift handover process as observed by the researcher. METHOD: The HTA was constructed using information gathered from interviews (n=13) describing the activities doctors said they should ideally perform in preparation for the shift handover meeting, during the meeting and after the meeting has finished. Observations (n=32) were made pre handover, during handover and post handover to capture the actual handover process in the acute medical assessment unit. Furthermore, a focus group discussion was included to validate the researcher's observations of the actual handover process and to provide content validity to the constructed HTA of the ideal handover process. RESULTS: Findings as represented by the HTA diagram showed the complexity of the process. The diagram revealed critical tasks that should be completed at each phase of the handover process, but observations revealed that these were sometimes omitted, mainly due to work demands and time pressure. These omissions were most apparent in the pre-handover stage, resulting in interrupted, extended and/or delayed handover meetings. CONCLUSION: The pre-handover phase is critical in providing a foundation for a thorough handover meeting and potentially helping doctors who have started a shift to prioritise patient care. These findings suggest that quality improvements for clinical handovers should include a designated time for preparation of care transfer information.